PEMBERDAYAAN MASYARAKAT KELURAHAN MERJOSARI, KECAMATAN LOWOKWARU, MALANG MELALUI PENINGKATAN KETRAMPILAN PENGOLAHAN PASCA PANEN - Dwi Susilowati (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The majority of the products produced by the residents' yards in RW 11 Merjosari, Lowokwaru Subdistrict, Malang City are horticulture and catfish commodities. Because the qualities of horticulture and catfish are easily damaged, post-harvest processing innovation is required. However, the community lacks expertise in good and correct post-harvest processing. The activity's goal is to increase abilities in post-harvest processing technology of horticulture commodities into juice and catfish processing into abon using a good and proper technique. The activities were carried out in the village of Merjosari, Lowokwaru District, Malang City, by the peasant organisation "Kenanga Kelurahan Merjosari" and the PKK RW 11 Merjosari. The activity stage begins with preparation, which includes socialising, problem identification, programme planning, and needs analysis. The second stage is training in the peasant group "Kenanga Kelurahan Merjosari" and PKK RW 11 Merjosari Village Lowokwaru District of Malang City, and the last stage is evaluation using questionnaires to measure improved horticultural and catfish processing abilities. The action lasted six months, beginning in June 2021. Every good activity generates a positive response from the community. Post-harvest horticulture processing skills, as well as catfish abon, are improving. This can be observed in the statistics, which shows that agricultural commodity processing abilities, which were initially just 10%, increased to 85%, while catfish processing skills, which were initially 13%, increased to 90%